Er3+-doped LuYSGG crystal as a potential 2.79 μm radiation-resistant laser material. (August 2022) - Zhang, Huili; Bian, Jintian; Sun, Dunlu; Luo, Jianqiao; Quan, Cong; Hu, Lunzhen; Han, Zhiyuan; Dong, Kunpeng; Cheng, Maojie; Chen, Yuwei
Highlights: Influence of 60 Co gamma-ray irradiation on the Er:LuYSGG crystal was demonstrated. Maximum average output power of 886 mW is achieved after irradiation. Maximum output power and slope efficiency are reduced by only 2.5% and 3.7%. Lifetime ratio between lower and upper laser levels is reduced after irradiation. Er:LuYSGG crystal is a potential 2.79 μm radiation-resistant laser material. Abstract: We demonstrate the influence of gamma-ray irradiation on the structure, spectroscopies, and laser performance of Er:LuYSGG crystal. After 100 Mrad 60 Co gamma-ray irradiation, the crystal structure remains unchanged, the absorption near 968 nm and emission within 2.7 ∼ 3 μm are almost unaffected, the level lifetimes are reduced, and the maximum output power of 886 mW is achieved with a maximum slope efficiency of 20.8%. The maximum output power and slope efficiency decrease by only 2.5% and 3.7% after irradiation, respectively, and the M 2 factor is little affected by irradiation. The results indicate that the Er:LuYSGG crystal is a potential mid-infrared radiation-resistant laser material applied in radiation environments.